Pendekatan Strategis dan Operasional Kontingen Garuda XXXIX-D MONUSCO dalam Menjaga Perdamaian Dunia - Muhammad Faizal Nasution; Agus Adriyanto; H.D. Arifin Simanjuntak H.D. Arifin Simanjuntak (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study analyzes the strategic and operational approaches of the Garuda Contingent XXXIX-D MONUSCO in maintaining world peace, focusing on logistics challenges, technology adoption, and military diplomacy. Using a descriptive qualitative method with SWOT analysis, the study identifies key weaknesses, including damaged logistics equipment, resource limitations, and reliance on international support. The findings highlight strategies such as enhancing international cooperation, adopting new technologies like drones, and implementing development and education programs in post-conflict areas. Training in logistics maintenance and personnel development is essential to strengthen operational readiness. The study also underscores the importance of a humanistic approach and local diplomacy to build trust with communities and enhance Indonesia's positive image globally. Despite advantages such as highly trained personnel and extensive experience, the contingent faces complex threats, including security risks and geographical constraints. In conclusion, the mission's success requires improved logistical support, technology integration and strengthened global collaboration. These strategies solidify Indonesia's role in international peacekeeping and support long-term stability and development in conflict-prone areas.